Indole-3-acetic acid biosynthesis and its regulation in plant-associated bacteria - Duca, Daiana R.; Glick, Bernard R. (Applied microbiology and biotechnology, 2020)
Numerous studies have reported the stimulation of plant growth following inoculation with an IAA-producing PGPB. However, the specific mode of IAA production by the PGPB is rarely elucidated. In part, this is due to the overwhelming complexity of IAA biosynthesis and regulation. The promiscuity of the enzymes implicated in IAA biosynthesis adds another element of complexity when attempting to decipher their role in IAA biosynthesis. To date, the majority of research on IAA biosynthesis describes three separate pathways classified in terms of their intermediates—indole acetonitrile (IAN), indole acetamide (IAM), and indole pyruvic acid (IPA). Each of these pathways is mediated by a set of enzymes, many of which are traditionally assumed to exist for that specific catalytic role. This lends the possibility of missing other, novel, enzymes that may also incidentally serve that function. Some of these pathways are constitutively expressed, while others are inducible. Some enzymes involved in IAA biosynthesis are known to be regulated by IAA or by IAA precursors, as well as by a multitude of environmental cues. This review aims to provide an update to our current understanding of the biosynthesis and regulation of IAA in bacteria. Key points • IAA produced by PGPB improves bacterial stress tolerance and promotes plant growth. • Bacterial IAA biosynthesis is convoluted; multiple interdependent pathways. • Biosynthesis of IAA is regulated by IAA, IAA-precursors , and environmental factors.